1991
DOI: 10.1001/jama.1991.03460200068037
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Density in Premenopausal Women Receiving Long-term Physiological Doses of Levothyroxine

Abstract: Total body and regional bone mineral density (BMD) levels were determined in 26 premenopausal women with Hashimoto's thyroiditis receiving long-term physiological doses of levothyroxine sodium replacement therapy. The BMD levels of each patient were compared with the mean of the BMD levels of age-matched normal controls. The mean levothyroxine sodium dose was 111 +/- 6 micrograms/d, and the mean duration of treatment was 7.5 +/- 5.3 years (range, 1 to 24 years). Dietary calcium intake was similar in both group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
1
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 22 publications
3
43
1
1
Order By: Relevance
“…Thus, our data did not confirm those of Kung and Pun [15] who found significantly lower BMD in regional skeleton in premenopausal women treated with replacement doses of L-T4 and no other risk factors for bone loss.…”
Section: Monthscontrasting
confidence: 99%
See 1 more Smart Citation
“…Thus, our data did not confirm those of Kung and Pun [15] who found significantly lower BMD in regional skeleton in premenopausal women treated with replacement doses of L-T4 and no other risk factors for bone loss.…”
Section: Monthscontrasting
confidence: 99%
“…In recent years, several reports recognised that chronic L-thyroxine (L-T4) therapy may be associated with reduced bone mass [10,20]. Some degree of L-T4 over-treatment leading to mild hyperthyroidism may be the cause of the decreased bone mass [8][9][10], but decreased bone density has also been found in premenopausal women with Hashimoto thyroiditis who received physiological doses of L-T4 [15].…”
Section: Introductionmentioning
confidence: 99%
“…No continuous overdosage of these medications was noted clinically or according to laboratory evaluations at the follow-up, but a previous minor overdosage of these two hormone substitutions cannot be excluded. This might have aggravated the bone loss (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have failed to confirm this decremental effect of L-T 4 treatment on BMD (14)(15)(16)(17) or on the prevalence of fracture (18,19). L-T 4 treatment that does not suppress TSH seems to have little effect on bone (20)(21)(22)(23). A recent, large prospective study on elderly ambulatory women found no consistent evidence that a low TSH concentration was associated with a low BMD or accelerated bone loss (2).…”
Section: Introductionmentioning
confidence: 99%